"Heritage" as alternative place and space: old-time music and roots- and routes-based tourism in Southern Appalachia. Issue 2 (15th March 2017) - Chaney, Ryan
ABSTRACT: After a decades-long exodus of industry and capital from Southern Appalachia, heritage tourism attempts to generate revenue by representing cultural authenticity in an area historically occupying the place of cultural backwater in American popular imaginations. This paper analyzes the representational terrain that such a tourism project traverses to present viable narratives of cultural authenticity. I suggest that valuations of authenticity in these representations, while exhibiting ambivalences about the values of the past and present, foreground iconic and indexical relationships among music, musicians, and Appalachian history and landscape, in turn drawing on the appeal of a different orientation to space and place. This appeal of and for a cultural and affective alternate route – an alternative to a high-speed, rootless, globalized landscape of mass consumption – is both opposed to and dependent on that landscape for its value and viability.